The role of SpyGlass Direct Visualization System on Patient with Indeterminate biliary strictures: A case report - Muhammad Miftahussurur; Manu Tandan; Dadang Makmun (Interna Publishing, 2022)
Biliary strictures diagnosis has become a challenge where benign conditions could mimic a malignant process. Recently, SpyGlass DS overcame the limitations by allowing direct visualization of the biliary tree. A 65 years old Indian patient complaints of jaundice with total and direct bilirubin of 23.3 mg/dL and 16.2 mg/dL, respectively. Liver function test, gamma-glutamyltransferase and CA 19-9 were increased. Transabdominal ultrasound and abdominal CT supported dilatation of common bile duct (CBD) with abrupt narrowing showing periductal enhancement at supra pancreatic level and stricture. Endoscopic ultrasound showed intrahepatic CBD stricture with dilated proximal CBD and sludge ball. Endoscopic retrograde cholangiopancreatography showed mid CBD stricture. Although brush cytology results suggested low grade dysplasia and no definite evidence of malignancy, cholangioscopy using SpyGlass DS found nodularity with abnormal vascularity seen in mid of CBD suggesting malignancy, confirmed with histopathology as cholangiocarcinoma. We reported additional value of SpyGlass DS for detecting cholangiocarcinoma in an indeterminate biliary stricture patient.